OPTIMIZATION OF PRODUCT MARKETING IN SHARIA BANKING THROUGH SOCIAL MEDIA - Indra Lesmana, Ceta; Haridah (Multifinance, 2023)
Islamic banking is a sector that continues to grow in Indonesia, with the aim of providing products and services that comply with sharia principles. Social media is one increasingly well-liked tool Islamic financial institutions use to market their goods. This research aims to explore the potential for optimizing product marketing in sharia banking through social media. This research uses a descriptive analytical method by collecting data through a literature study and analysis of social media content used by Islamic financial institutions in Indonesia. The research results show several problems related to optimizing product marketing in sharia banking via social media, including content incompatibility with sharia principles, credibility of sharia financial institutions, public misunderstanding of sharia banking products, controversy and negative perceptions, as well as consumer protection. To overcome this problem, this research also identifies several strategies that can be used by Islamic financial institutions to optimize product marketing on social media.